Analisis Implementasi Pelatihan Komunikasi Interpersonal Penggiat Anti Narkoba - Novianti, Herny (UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to analyze the implementation of interpersonal communication training for anti-drug activists in entrepreneurial circles, Cirebon city. The research method uses a combined method evaluation model between quantitative methods and qualitative methods (mixed-method), precisely explanatory mixedmethod design. Data collection uses interpersonal communication instruments which include: 1) openness; 2) empathy; 3) support; 4) positive attitude; 5) equality of will and communication. Overall it can be said that the interpersonal communication skills of anti-drug activists in the entrepreneurial environment of Cirebon City are in the